DEVELOPMENT AND ANALYSIS OF THE PAPER SUPPORT ROLLER AND SHAFT ASSEMBLY FOR EFFICIENT OPERATION IN A PAPER SLITTER-REWINDER MACHINE - Jagtap, Ganesh; Patil, Gajendra Vasantrao (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study covers the design modification required to achieve adequate support to the paper while slitting operation is in progress. The problem was arrived at the manufacturer of digital printing papers,. Wherein, the existing paper support shaft assembly of a paper slitting machine was not fulfilling the purpose of opening the slitted gap of the paper in order to obtain the smaller paper rolls of varying sizes from a big parent paper roll of 1.5 meter. Herein, observations have been done on existing paper support assembly to identify the root cause; Design and development of modified paper support shaft assembly have been successfully performed to overcome the problem of improper slitting operation.